2018
DOI: 10.1101/448951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutualism outcome across plant populations, microbes, and environments in the duckweedLemna minor

Abstract: 1The picture emerging from the rapidly growing literature on host-associated micro-2 biota is that host traits and fitness often depend on complex and interactive effects 3 of host genotype, microbial interactions, and abiotic environment. However, testing 4 these main and interactive effects typically requires large, multi-factorial experiments 5 and thus remains challenging in many systems. Furthermore, most studies of plant 6 microbiomes focus on terrestrial hosts and microbes. Aquatic habitats may confer 7… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…It has a nearly cosmopolitan distribution (RDSC, ) and is widespread in the Greater Toronto Area, including in stormwater ponds and other water bodies that are commonly exposed to runoff. Duckweeds have microbial communities living on or in their roots and fronds, and our previous work has found that experimental microbial inoculation of sterilized L. minor increases plant growth (O'Brien et al., [Preprint]).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has a nearly cosmopolitan distribution (RDSC, ) and is widespread in the Greater Toronto Area, including in stormwater ponds and other water bodies that are commonly exposed to runoff. Duckweeds have microbial communities living on or in their roots and fronds, and our previous work has found that experimental microbial inoculation of sterilized L. minor increases plant growth (O'Brien et al., [Preprint]).…”
Section: Methodsmentioning
confidence: 99%
“…We prepared microbial inocula from each site by swabbing across the stored agar plate, adding to yeast mannitol broth, culturing in a shaking incubator (VWR, Radnor, PA, USA) for 3 d at 30°C and 200 rpm, and diluting to control cell density across inocula. We prepared dilutions by measuring optical density, converting to cell counts by applying a single calibration curve across inocula (correlated to colony forming units, O'Brien et al., [Preprint]), and standardizing to approximately 3000 cells/μL. The exact relationship of optical density to cell count depends on both cell size and composition (Volkmer and Heinemann, ), both of which likely vary across the taxa in our cultures, so cell concentrations may differ slightly across inocula.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a nearly cosmopolitan distribution (RDSC, 2016), and is widespread in the Greater Toronto Area, including in stormwater ponds and other water bodies that are commonly exposed to runoff. Duckweeds have microbial communities living on or in their roots and fronds, and our previous work has found that experimental microbial inoculation of sterilized L. minor increases plant growth (O’Brien et al, 2018).…”
Section: Methodsmentioning
confidence: 99%